The theme of tragedy in modern Uzbek poetry (in works of Halima Ahmedova, Zebo Mirzo, Nodira Afokova) - D.V.Abdusalomova (Zien Journals, 2022)
The article examines the extent of tragedy in the work of our Uzbek female poets and highlights its general aspects
Keywords: Uzbek poetry; analysis of poems by Uzbek female poets; tragedy; tragedy in lyrics